2019
DOI: 10.1186/s12882-019-1358-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of immunosuppression on postoperative graft function after graft-unrelated surgery: a retrospective controlled cohort study

Abstract: Background Physicians are faced with a growing number of patients after renal transplantation undergoing graft-unrelated surgery. So far, little is known about the postoperative restitution of graft function and the risk factors for a poor outcome. Methods One hundred one kidney transplant recipients undergoing graft-unrelated surgery between 2005 and 2015 were reviewed retrospectively. A risk analysis was performed and differences in creatinine, GFR and immunosuppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…These results are convenient with most of the studies that concluded QOL in patients after renal transplantation showed a good level for everyday life functioning comparing with other treatment options for ESRD. [2][3][4] These findings interpreted in light of renal transplant recipients are freer in terms of diet and travel than any patient on dialysis. [30] In addition, other studies concluded that renal transplantation stays the best option in the management of patients with end-stage renal disease (ESRD) as it gives the best potential quality of life, less morbidity and mortality, and great cost savings in the long term for patients with ESRD.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…These results are convenient with most of the studies that concluded QOL in patients after renal transplantation showed a good level for everyday life functioning comparing with other treatment options for ESRD. [2][3][4] These findings interpreted in light of renal transplant recipients are freer in terms of diet and travel than any patient on dialysis. [30] In addition, other studies concluded that renal transplantation stays the best option in the management of patients with end-stage renal disease (ESRD) as it gives the best potential quality of life, less morbidity and mortality, and great cost savings in the long term for patients with ESRD.…”
Section: Discussionmentioning
confidence: 85%
“…[2] Renal transplantation is considered the safest and the best current management option for patients with end-stage renal disease (ESRD) because it prolongs a patient's life, decreases morbidity, and consequently improves the quality of life (QOL). [3,4] On the other hand, researchers [5][6][7][8] agreed that renal transplantation is becoming the first line of management for patients with ESRD, regardless of age, when compared to renal dialysis. Kidney transplantation increases life expectancy, as well as improves both patient's physical and social functioning (quality of life), as well as intellectual stability, energy, and the overall well-being and the upcoming outlook.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, CNI drugs such as tacrolimus and cyclosporine A are the most common nephrotoxic drugs [ 26 , 27 ]. However, the risk of kidney injury was significantly lower in patients treated with the combination of tacrolimus and mycophenolate mofetil (MMF) [ 28 ]. In addition, reducing the dose of CNI used through combination therapy may effectively reduce the incidence of AKI and CKD without increasing the risk of rejection [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%